2019
DOI: 10.1186/s12929-019-0561-6
|View full text |Cite
|
Sign up to set email alerts
|

Natural outer membrane permeabilizers boost antibiotic action against irradiated resistant bacteria

Abstract: Background This study sought to develop new strategies for reverting the resistance of pathogenic Gram-negative bacilli by a combination of conventional antibiotics, potent permeabilizers and natural beta lactamase inhibitors enhancing the activity of various antibiotics. Methods The antibiotic susceptibility in the presence of natural non-antibacterial tested concentrations of phytochemicals (permeabilizers and natu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(33 citation statements)
references
References 26 publications
1
32
0
Order By: Relevance
“…Nonetheless, as far as we know, scarce data are available about its antimicrobial activity against MDR A. baumannii. Gallic acid is a phenolic acid with reported antibacterial activity, especially in combination with conventional antibiotics ( Shao et al, 2015 ; Dos Santos et al, 2018 ; Farrag et al, 2019 ). Notably, the mean minimal effective dose of cinnamic acid (1.2 mg/ml) was significantly lower than that of gallic acid (1.67 mg/ml).…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, as far as we know, scarce data are available about its antimicrobial activity against MDR A. baumannii. Gallic acid is a phenolic acid with reported antibacterial activity, especially in combination with conventional antibiotics ( Shao et al, 2015 ; Dos Santos et al, 2018 ; Farrag et al, 2019 ). Notably, the mean minimal effective dose of cinnamic acid (1.2 mg/ml) was significantly lower than that of gallic acid (1.67 mg/ml).…”
Section: Discussionmentioning
confidence: 99%
“…No significant dose response was detected in case of E. coli, while with Salmonella cells a dose dependent response was detected, suggesting that with the increase of the peptide concentration the membrane destabilized increasing its permeability. When Salmonella cells were treated with 2× MIC peptide and the ONP release was monitored over time (30,60,80, 100, and 120 min), we observed that the steady-state level of β-galactosidase was recorded at 60 min and remained constant while in case of E. coli the steady state level was reached at 100 min (data not shown). However, the increase of cytoplasmic membrane permeabilization may correlate with the membrane disruption, leading to leakage of cell cytoplasmic content and cell death.…”
Section: Peptide Utngt21o Permeated the Target Cell Membranementioning
confidence: 90%
“…After the complete genome was assembled, BLAST analysis was carried out to identify to which species each scaffold showed similarity. Out of 31 contigs analyzed 20 contigs hits matched the core genome of different groups within Weissella and for 11 contigs (15,17,21,23,24,(26)(27)(28)(29)(30)(31) no match was shown in database ( Table S4). The largest contig 1 of the subject query (UTNGt21O) hits W. cibaria genome with an 83 percentage of identity with no gaps (0).…”
Section: Genome Assembly and Taxonomic Classificationmentioning
confidence: 99%
See 1 more Smart Citation
“…In Gram-negative bacteria, the peptidoglycan layer (susceptible layer) is protected by a less permeable outer membrane. Various strategies have been adopted to address this issue, including the use of outer membrane permeabilizers such as EDTA, gallic acid, and thymol in combination with endolysins in Gram-negative bacteria to provide significant results [ 169 ]. permeablilizer…”
Section: Insights Into the Clinical Trials Of Engineered Endolysimentioning
confidence: 99%